Maternal body mass index, gestational weight gain, and the risk of overweight and obesity across childhood: An individual participant data meta-analysis - Trnovec T.; Tough S.; van Rossem L.; Turner S.; Vrijheid M.; von Berg A.; West J.; Vrijkotte T.; Ronfani L.; Rifas-Shiman S.; Standl M.; Santos A.; et al. (NLM (Medline), 2022)
Maternal obesity and excessive gestational weight gain may have persistent effects on offspring fat development. However, it remains unclear whether these effects differ by severity of obesity, and whether these effects are restricted to the extremes of maternal body mass index (BMI) and gestational weight gain. We aimed to assess the separate and combined associations of maternal BMI and gestational weight gain with the risk of overweight/obesity throughout childhood, and their population impact